PENGARUH PENGGUNAAN TIPE NHT BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI - Saputri, Detri; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of the use of number head together type assisted by audio-visual media on essay writing skills in the description of grade V students of Public Elementary School 22 West Pontianak. The method used is an experimental method with a quasi-experimental form of nonequivalent control group design. The population in this study is class V of Public Elementary School 22 West Pontianak. The sample in this study was class V A which amounted to 34 students as a control class and class V B which amounted to 34 students as an experimental class. Data was collected using measurement techniques using tools in the form of tests with a written test form of 1 question. After t test is obtained t_count (4.739) and t_ (table) (Î± = 5% and dk = 34 + 34â€“2 = 66) is 2,002. Because t_count (4,739)> t_tabel (2,002), thus H0 is rejected and Ha accepted. From the results of the calculation of effec size (ES), by ES is 0.95 with the criteria classified as high. This means learning with the use of type head together with the help of audiovisual media gives a high influence on the writing skill of the description of the fifth grade students of West Pontianak 22 State Elementary School.Â Keywords: Type Number Head Together, Audiovisual Media, Writing Skills, Essay Description.